Fisheries and habitat investigations of tributary streams in the southern portion of the AOSERP study area: Volume II ... - Tsui, P. T. P.; Tripp, D. B. (University of Alberta Library, 1980)
This report presents the results of studies conducted from May to October 1978 on tributary streams in the southern portion of the AOSERP study area. The major objectives of these investigations were: 1. To describe the baseline states of the major components of the aquatic ecosystems in the southern portion of the AOSERP study area; 2. To describe, in detail, aquatic habitats of the southern portion of the AOSERP study area; and 3. To provide a quantitative estimate of the biological significance of the watersheds to the Athabasca River system. Three streams, the Christina, Gregoire, and Hangingstone, were selected for detailed study and were examined in early and late spring, late summer, and late autumn. Together, these three streams are representative of most of the major stream habitat types occurring within the project study area. Other waterbodies were sampled once only during late summer. This report consists of two volumes. Volume I is an explanatory text complete with summary tables and maps, while ...